Prenatal exposure to opioids and neurodevelopment in infancy and childhood: A systematic review - Balalian, Arin A.; Graeve, Richard; Richter, Matthias; Fink, Astrid; Kielstein, Heike; Martins, Silvia S.; Philbin, Morgan M.; Factor-Litvak, Pam (Frontiers in Pediatrics, 2023)
Abstract Aim This systematic review aims to estimate the relationship between prenatal exposure to opioids and neurodevelopmental outcomes and examines potential sources of heterogeneity between the studies. Methods We searched four databases through May 21st, 2022: PubMed, Embase, PsycInfo and the Web of Science according to a specified search strings. Study inclusion criteria include: 1) cohort and case-control peer-reviewed studies published in English; 2) studies comparing neurodevelopmental outcomes among children with prenatal opioid-exposure (prescribed or used non-medically) versus an unexposed group. Studies investigating fetal alcohol syndrome or a different primary prenatal exposure other than opioids were excluded. Two main performed data extraction using “Covidence” systematic review platform. This systematic review was conducted in accordance with PRISMA guidelines. The Newcastle-Ottawa-Scale was used for quality assessment of the studies. Studies were synthesized based on the type of neurodevelopmental outcome and the instrument used to assess neurodevelopment. Results Data were extracted from 79 studies. We found significant heterogeneity between studies due to their use of different instruments to explore cognitive skills, motor, and behavioral outcomes among children of different ages. The other sources of heterogeneity included: procedures to assess prenatal exposure to opioids; period of pregnancy in which exposure was assessed; type of opioids assessed (non-medical, medication used for opioid use dis-order, prescribed by health professional), types of co-exposure; source of selection of prenatally exposed study participants and comparison groups; and methods to address lack of comparability between exposed and unexposed groups. Cognitive and motor skills as well as behavior were generally negatively affected by prenatal opioid exposure, but the significant heterogeneity precluded a meta-analysis. Conclusion We explored sources of heterogeneity in the studies assessing the association between prenatal exposure to opioids and neurodevelopmental outcomes. Sources of heterogeneity included different approaches to participant recruitment as well as exposure and outcome ascertainment methods. Nonetheless, overall negative trends were observed between prenatal opioid exposure and neuro-developmental outcomes.